Kurdish EFL Learners’ Awareness of Passivization in English and Kurdish - Ahmed, Salih Ibrahim (Universitas Islam Negeri Raden Intan Lampung, 2022)
Passivization is the grammatical process in which the structures of the whole sentence, and specifically the verb phrase, change. This process is one of the main syntactic needs in any academic writing. Therefore, any English learner needs to know enough about it by the end of undergraduate studies. This paper, being an empirical one, tests Kurdish learners’ awareness of the process by providing an instrument. The data and the scope of the study are sentences from English and Kurdish. A cohort of eightyeight senior students in the English departments in Iraqi Kurdistan universities were selected randomly to participate in the study. As for the Kurdish variety, the Central Kurdish has been chosen which is spoken in Erbil and Sulaymania. On this basis, the setting of the research incudes only the universities situated in this geographical area. A mixed method has been adopted in doing the paper. The aim of the study is to indicate and compare the learners’ awareness in passivizing and recognizing certain sentence structures in both languages. One of the main conclusions of the study is that there is a positive correlation between the EFL learners’ awareness in English and Central Kurdish (CK) in relation to passivization.